Governance quality and tax compliance behaviour in East Malaysia - Mohd Allif Anwar Abu Bakar; Mohd Rizal Palil; Ruhanita Maelah (Penerbit Universiti Kebangsaan Malaysia, 2021)
In this paper, we examine the relationship and links between the governance quality and tax compliance behaviour across taxpayers in East Malaysia otherwise known as Borneo. The hypotheses were tested using structural equation modelling of partial least squares. Four proxies of governance quality were examined in the study, namely, Voice and Accountability (VA), Political Stability (PS), Government Effectiveness (GE), and Rule of Law (RL). Results indicate that only political stability and rule of law are found to significantly influence tax compliance behaviour positively, while the other two proxies of voice and accountability and government effectiveness showed otherwise with insignificant findings. The current finding suggests that the government should maintain stability in the political system and promote a stringent with the effective rule of law to encourage substantial participation in tax compliance behaviour.